2011
DOI: 10.1073/pnas.1019041108
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes engineered to activate the Nlrc4 inflammasome are severely attenuated and are poor inducers of protective immunity

Abstract: Inflammasomes are intracellular multiprotein signaling complexes that activate Caspase-1, leading to the cleavage and secretion of IL-1β and IL-18, and ultimately host cell death. Inflammasome activation is a common cellular response to infection; however, the consequences of inflammasome activation during acute infection and in the development of long-term protective immunity is not well understood. To investigate the role of the inflammasome in vivo, we engineered a strain of Listeria monocytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
191
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(206 citation statements)
references
References 41 publications
14
191
1
Order By: Relevance
“…Thus, findings of our present study extended the mechanistic understanding of the IL-18 function. The NLRC4 inflammasome has been shown to contribute to host defense against a L. monocytogenes strain engineered to secrete Legionella pneumophila flagellin, which strongly and rapidly induces inflammasome activation and host cell death in an NLRC4-dependent manner, while this inflammasome is dispensable for defense against its parental strain [21]. This suggests that hyperactivation of the inflammasome is deleterious to L. monocytogenes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, findings of our present study extended the mechanistic understanding of the IL-18 function. The NLRC4 inflammasome has been shown to contribute to host defense against a L. monocytogenes strain engineered to secrete Legionella pneumophila flagellin, which strongly and rapidly induces inflammasome activation and host cell death in an NLRC4-dependent manner, while this inflammasome is dispensable for defense against its parental strain [21]. This suggests that hyperactivation of the inflammasome is deleterious to L. monocytogenes.…”
Section: Discussionmentioning
confidence: 99%
“…A protective role of caspase-1 in systemic L. monocytogenes infection has been demonstrated [20]. Moreover, a recent study has shown that a L. monocytogenes strain engineered to secrete Legionella flagellin, an NLRC4 agonist, strongly induces inflammasome activation and is severely attenuated in vivo in an NLRC4-dependent manner [21]. It has also been reported that the impact of IL-1R deficiency on resistance of mice to L. monocytogenes varies with the genetic background of the host and infection route.…”
mentioning
confidence: 98%
“…While motility in the host is advantageous for navigation of the gastrointestinal tract and host-cell targeting, secretion of flagellin or the presence of a flagellum triggers the inflammasome and can result in subsequent clearance by the immune system. 30,31 In L. monocytogenes, flagellar motility is thermo-regulated by the action of an anti-repressor protein called GmaR, which is also an O-linked N-acetylglucosamine transferase responsible for posttranslational modification of flagellin with up to six molecules of β-O-GlcNAc. 32 GmaR becomes unstable at the non-permissive growth temperature (37 °C) and dissociates from the motility operon repressor, MogR, thus resulting in downregulation of motility.…”
Section: Loss Of Lyspgs Causes No Significant Effect On Protein Localmentioning
confidence: 99%
“…Thus, we are able to study how preferential activation of cell death pathways in myeloid-derived antigen-presenting cells influences the development of immunity. To activate pyroptosis, we utilized a previously described strain of L. monocytogenes (Lm-pyro) that triggers the Nlrc4 inflammasome via the ectopic secretion of flagellin (34). Upon infection of wild-type bone marrow-derived macrophages (BMDMs) or granulocyte-macrophage colony-stimulating factor (GM-CSF)-stimulated cells (referred to as bone marrow-derived dendritic cells [BMDCs]), strain Lm-pyro triggered robust lytic host cell death as measured by lactate dehydrogenase (LDH) release (Fig.…”
mentioning
confidence: 99%